The Effectiveness of Social Media Advertisement in The Indonesian Sneakers Industry: Application of The Extended Advertising Value Model - Alvin Achmad; Antonius Indra Saputra; Aulia Fadhil Ardiansyah; Evelyn Hendriana (Universitas Mercu Buana, 2022)
Objectives: This study aims to examine the effect of social media advertising values on customer engagement and purchase intention. Despite the unique features of social media ads to generate customer engagement, there is not much research that combines the advertising value model and interactivity component to understand the effectiveness of social media ads.Methodology: Questionnaires were distributed to followers of sneaker brands’ Instagram official account in Greater Jakarta who had bought the sneakers. There were 314 responses analyzed by PLS-SEM to answer the research questions.Finding: The results showed that customer engagement was influenced by credibility, entertainment, and interactivity of the advertisement, which eventually led to purchase intention. Furthermore, entertainment and interactivity advertising values had a direct influence on purchase intention.Conclusion: Brands should create entertaining and interactive ads to trigger engagement with their followers and stimulate their desire to purchase the products. Practical insights are provided based on these research findings.